An update on obesity research pattern among adults in Malaysia: a scoping review - Noor Safiza Mohamad Nor; Rashidah Ambak; Norazian Mohd Zaki; Nur Shahida Abdul Aziz; Siew Man Cheong; Mohamad Aznuddin Abd Razak; Muslimah Yusof; Mohamad Hasnan Ahmad; Azli Baharuddin; Megat Rusydi Megat Radzi; Wan Nur Khairunnisa Wan Kozil; Intan Hafizah Ishak; et al. (BMC, 2018)
Abstract Background Obesity is a global health burden in the non-communicable diseases and much efforts have been implemented in the past decade in response to the rise of obesity prevalence among the Malaysian population. These include the development of the national policies, health programmes and research activities. The main aim of the scoping review was to identify obesity research pattern among adults in Malaysia in terms of the scopes, topics and the research designs. Methods The scoping review was conducted based on the framework by Arksey and O'Malley. The Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) diagram was used as a guide to record the review process. Articles from year 2008 until 2017 on overweight and obesity among adults aged 18 years and above were retrieved based on the keywords using electronic databases (Embase/Ovid, Pubmed, Cochrane library and Google Scholar). Local journals, Nutrition Research in Malaysia Biblography (2011 and 2016), online local theses databases, virtual library databases were also included in the searches. Consultations with relevant key informants from the National Institutes of Health and local universities were also conducted. Search activities were managed using Endnote software and MS Excelsheet. Results The characteristics of the results were described based on the objectives of the review. A total of 2004 articles and reports were retrieved, and 188 articles related to obesity in Malaysia were included in the final review. Scopes and topics of obesity research based on the Nutrition Research Priorities in Malaysia (NRPM) for 11th Malaysia Plan were obesity prevalence, weight loss intervention, association of physical activities and dietary factors with obesity. The majority of obesity research among adults in Malaysia was cross sectional studies and only a small number of intervention studies, qualitative studies and systematic review were indentified. Research gaps were identified in order to make useful recommendations to the stakeholders. Conclusions In the past decade, there has been an emerging evidence on obesity research among adults in Malaysia. More obesity research needs to be conducted particularly on obesity intervention among specific gender, qualitative studies, economic cost and genetic factors of obesity.